1994
DOI: 10.1007/bf02353627
|View full text |Cite
|
Sign up to set email alerts
|

Family structure, family organization, and quality of family life

Abstract: This study examines how family organization is associated with the quality of family life for parents in first marriages, remarriages with biological children, and several types of stepfamilies. Data are drawn from the 1987-1988 National Survey of Families and Households; only married couples in which both spouses participated in the survey and who had children under age 19 in the household are considered (N ---3,120). Results indicate that respondents in different family structures differ in the perceived qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Hence, one should control for occupational status when analyzing the effect of monetary resources. Previous studies, however, generally have found weak or inconsistent effects of parental resources such as income and education on relations with biological and social offspring (Henretta et al, ; King, ; Voydanoff et al, ; Ward et al, ). One study that used a direct measure of the perceived relative difficulty of finding satisfaction with stepchildren (MacDonald & DeMaris, ) found that higher parental education slightly reduced the stepgap.…”
Section: What Narrows the Stepgap? Theoretical Considerations And Eximentioning
confidence: 98%
See 2 more Smart Citations
“…Hence, one should control for occupational status when analyzing the effect of monetary resources. Previous studies, however, generally have found weak or inconsistent effects of parental resources such as income and education on relations with biological and social offspring (Henretta et al, ; King, ; Voydanoff et al, ; Ward et al, ). One study that used a direct measure of the perceived relative difficulty of finding satisfaction with stepchildren (MacDonald & DeMaris, ) found that higher parental education slightly reduced the stepgap.…”
Section: What Narrows the Stepgap? Theoretical Considerations And Eximentioning
confidence: 98%
“…A number of studies have shown a stronger cohesion of biological versus social parent–child ties in terms of emotional bonds such as feelings of closeness (Aquilino, ; Brown & Manning, ; Kurdek & Fine, ; Lansford et al, ; Voydanoff, Fine, & Donnelly, ; Zill, Morrison, & Coiro, ), contact (Aquilino, ), filial obligations (Aquilino, ), mutual support (Amato, Rezac, & Booth, ), and time and money transfers (Henretta, Soldo, & Van Voorhis, ; Pezzin, Pollak, & Schone, ). Longitudinal studies have indicated that stepparents, especially those who do not have biological children, seem to become less involved over time (Stewart, ), although this effect may be attributable to the fact that involvement declines as children grow older, coupled with the higher mean age of stepchildren compared to biological offspring (Teachman & Tedrow, , p. 17).…”
Section: The Stepgap: Concepts and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Family routine refers to the level at which parents provide structure, consistency, and organization in the home environment (Voydanoff et al 1994) and has been examined across developmental periods spanning from preschool to adolescence (e.g., Brody and Flor 1997; Koblinsky et al 2006; Taylor 1996). Given this description, child-reported family routine may be especially important among children exhibiting higher levels of impulsivity.…”
mentioning
confidence: 99%
“…My work with Larry Kurdek (e.g., Fine & Kurdek, 1995;Kurdek & Fine, 1991), trained as a developmental psychologist, and also with Patricia Voydanoff and Brenda Donnelly (e.g., Fine, Voydanoff, & Donnelly, 1993;Voydanoff, Fine, & Donnelly, 1994), both sociologists, illustrates research collaborations that were primarily interdisciplinary in the sense that we: (a) did not divide up research tasks according to disciplinary affiliation, (b) most of the important tasks could be performed by any of the research partners, (c) and we were as likely to submit to multidisciplinary journals (e.g., Journal of Marriage and the Family) as we were to disciplinary ones (e.g., Journal of Family Psychology). Nevertheless, there were some tasks that were assigned on the basis of disciplinary training and/or expertise, such as when I, because of my clinical background and experience, would be more likely to write "implications for practitioners" sections of manuscripts, whereas my sociologist collaborators would be more likely to integrate a sociological theory into a manuscript.…”
Section: Marriage and Family Reviewmentioning
confidence: 99%